Smelting of low-grade saprolitic nickel ore in DC-Arc furnace - Nurjaman, Fajar; Zul Hakim, Hafid; Septiansyah, Bagus; Arham, La Ode; Handoko, Anton Sapto; Bahfie, Fathan; Suherman, Ijang; Haryadi, Harta; Suseno, Triswan; Sari, Yuliana; Suharno, Bambang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Most nickel laterite smelting to produce ferronickel is carried out using an AC-arc furnace. Although the DC-arc furnace is advantageous in the smelting of fine ore, it is rarely used for nickel laterite. In this work, the effects of slag basicity and stoichiometry of reductant addition during smelting of low-grade saprolitic nickel ore on nickel content and nickel recovery, yield, and phases of the slag were studied in detail. The smelting process was conducted in a laboratory DC-arc furnace with a a single electrode of 30 cm diameter. A 5 kg of low-grade saprolitic nickel ore (1.92 Ni-12.97 Fe), some coke as reductant, and some limestone as flux were smelted in a DC-arc furnace for about one hour. The pouring temperature of hot metal and slag was 1400-1500 °C. The basicity of the quaternary slag of 0.8   and the stoichiometric carbon of 0.8 of the reductant resulted in an optimum smelting process of nickel ore in a DC-arc furnace, producing ferronickel with a Ni content of 14.59% with 92.26% recovery.
Keywords: nickel ore, smelting, DC-arc furnace, ferronickel